Thiopurine Biotransformation and Pharmacological Effects: Contribution of Oxidative Stress. - Pelin, Marco; De Iudicibus, Sara; Londero, Margherita; Spizzo, Riccardo; Dei Rossi, Sveva; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Curr Drug Metab, 2016)
BACKGROUND: Thiopurine antimetabolites are important agents for the treatment of severe diseases, such as acute lymphoblastic leukemia and inflammatory bowel disease. Their pharmacological actions depend on biotransformation into active thioguanine-nucleotides; intracellular metabolism is mediated by enzymes of the salvage pathway of nucleotide synthesis and relies on polymorphic enzymes involved in thiopurines' catabolism such as thiopurine-S-methyl transferase. Given the enzymes involved in thiopurines' metabolism, it is reasonable to hypothesize that these drugs are able to induce significant oxidative stress conditions, possibly altering their pharmacological activity. METHODS: A systemic search of peer-reviewed scientific literature in bibliographic databases has been carried out. Both clinical and preclinical studies as well as mechanistic studies have been included to shed light on the role of oxidative stress in thiopurines' pharmacological effects. RESULTS: Sixty-nine papers were included in our review, allowing us to review the contribution of oxidative stress in the pharmacological action of thiopurines. Thiopurines are catabolized in the liver by xanthine oxidase, with potential production of reactive oxidative species and azathioprine is converted into mercaptopurine by a reaction with reduced glutathione, that, in some tissues, may be facilitated by glutathione- S-transferase (GST). A clear role of GSTM1 in modulating azathioprine cytotoxicity, with a close dependency on superoxide anion production, has been recently demonstrated. Interestingly, recent genome-wide association studies have shown that, for both azathioprine in inflammatory bowel disease and mercaptopurine in acute lymphoblastic leukemia, treatment effects on patients' white blood cells are related to variants of a gene, NUDT15, involved in biotransformation of oxidated nucleotides. CONCLUSIONS: Basing on previous evidences published in literature, oxidative stress may contribute to thiopurine effects in significant ways that, however, are still not completely elucidated.